Class, capital, and competing academic discourse: a critical analysis of the mission/s of American higher education. Issue 1 (2nd January 2016) - Stich, Amy Elizabeth; Reeves, Todd D.
Abstract : In this paper, we critically analyze institutional mission statements as discursive texts replete with symbolic meaning, as we believe these texts reveal a great deal about the ways in which higher education remains increasingly stratified. We argue that beneath the generalized rhetoric of institutional mission statements, lie powerful messages seemingly coded with varying forms of class-based academic capital. We further argue that these messages reflect two distinct, competing discourses surrounding the purpose and value of higher education, that parallel the stratification of the larger system itself. Findings reveal evidence of these competing discourses and contribute to larger discussions surrounding educational inequality.